The propensity to patent with horizontally differentiated products: An empirical investigation - Diana Heger; Alexandra K. Zaby (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2009)
In this paper we empirically investigate the theoretical results obtained in Zaby (2009). From the theoretical model, which introduces the decision to patent into a setting with horizontally differentiated products we deduce several hypotheses and test these empirically. We find that the propensity to patent increases when market entry costs decrease. Furthermore, if the disclosure requirement linked to a patent has an impact, the propensity to patent decreases with the strength of the disclosure effect.
urn:nbn:de:bsz:21-opus-43590
Keywords: L13; O14; O33; O34; 330; patenting decision; secrecy; disclosure requirement; market entry; horizontal product differentiation; Innovation; Patent; Geheimhaltung; Lizenzvergabe; Produktdifferenzierung; Markteintritt; Schätzung; Deutschland